Seismic vulnerability of masonry buildings: Numerical insight on damage causes for residential buildings by the 2016 central Italy seismic sequence and evaluation of strengthening techniques. (March 2020) - Acito, Maurizio; Magrinelli, Eleonora; Milani, Gabriele; Tiberti, Simone
Abstract: This study aims at investigating the causes of damage and collapse of several residential masonry structures during the devastating seismic sequence that hit Central Italy in 2016. After analyzing the structural features of affected buildings, an extensive series of numerical analyses is performed for a sample two-story masonry building to better understand its seismic vulnerability and suggest valuable hints for the reconstruction of historical city centers. Each analysis is carried out by adopting realistic hypotheses concerning material properties, connection among multi-leaf walls, different roofing systems (e.g., use of RC slabs at the top of the buildings), and the presence of rigid or flexible floors. Numerical analyses consist of modal and non-linear dynamic analyses, the latter using input accelerograms recorded during the main shocks of 2016 by the permanent accelerometric station of Amatrice (one of the most affected municipalities). For non-linear dynamic analyses, an elasto-plastic constitutive law with reasonable damage parameters in tension is adopted. Numerical results highlight good correspondence with observed behavior of residential low-rise buildings after the main seismic events in Amatrice, demonstrating the validity of the numerical approach. Moreover, the poor quality of the constitutive masonry material and the insufficient rigidity of floors and roofing systems are identified as the main causes of seismic vulnerability and, consequently, of collapse mechanisms. It is found that high quality masonry and well-connected walls play a crucial role in limiting damage formation and reducing global seismic vulnerability. Highlights: Behavior under seismic actions of typical Central Italy masonry residential buildings. Identification of vulnerable macro-elements with 3D FE Non-linear dynamic analyses NLDAs. Damage-plasticity with softening in tension and compression material used to model masonry. Application of repeated accelerograms belonging to Central Italy 2016 seismic sequence. Sensitivity analysis on effects induced by possible strengthening interventions.